Health Awareness Raising with ‘5 Minutes Workout’ Digital Campaign - Darmawan, Andreas James; Suryawati, Ni Putu; Utami, Sri (RSF Conference Series: Business, Management and Social Sciences, 2021)
Health Awareness is important to have a healthy body and good physical fitness. It is something that must be maintained, especially in the post-pandemic period. Another factor that triggers people to ignore health and physical fitness is because it is considered to waste time and there are not many health sports models whose implementation is simpler and shorter. Therefore, a solution is needed in the form of a campaign about short exercise for 5 minutes that can be done at home or office. The method of collecting data for this digital campaign is though observation method, observing one of the sports fields in Denpasar, also by distributing questionnaires, and by interviewing 3 people. The results will be used as basic design concept, and will be digitally campaigned in form of active and healthy short exercises. Campaign will be compiled with digital media in application, with the style of pop art design in order to gain ’5 Minutes Workout’ campaign.